Profiles of functioning of a group of children with cerebral palsy in Argentina: Preliminary data from the first national study - Escobar, L. Johana (2024)
Fil: Escobar, L. Johana. Universidad Nacional de Córdoba. Facultad de Ciencias Médicas; Argentina.